An unusual presentation of sphenochoanal polyp - Joseph, Lini; Prasad, Kothegala C.; Koneru, Prathyusha; Varsha, Indu; Karunasagar, Abhilasha; Pilakkilakkandiyil, Anjali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Sphenochoanal polyp is a rare entity. Isolated polyps arising from mucosa covering the anterior wall of the sphenoid sinus or sphenoethmoidal recess extending till oropharynx is extremely rare. We aim to report a rare case of sphenochoanal polyp with a slender, unusually long stalk which extended till nasopharynx leading to a large bulky polypoidal mass extending till oropharynx. Due to its posterior location, sphenochoanal polyps are often diagnosed late as they can be easily missed in clinical examination. We intend to emphasize the combined use of diagnostic nasal endoscopy and computed tomography imaging in patients presenting with unilateral or bilateral nasal obstruction, snoring and recent onset of sleep disturbances. Treatment includes endoscopic excision of polyp and cauterization of the base of the stalk. Widening of the sphenoid sinus ostium is done when necessary. Early and complete removal and regular follow up is essential to prevent complications.